Beyond Legal Protection: Patriarchal Culture, the Justice Gap, and Domestic Violence in Indonesia - M. Ridha Rahmat Putra; Ferdi Yufriadi (Yayasan Lembaga Studi Makwa, 2026)
This study aims to examine how patriarchal culture and the justice gap influence the implementation of legal protection against domestic violence in Indonesia and to evaluate their implications for the development of contemporary Islamic family law. This research employs an empirical legal approach through qualitative field research. Primary data were collected through in-depth interviews with victims of domestic violence, law enforcement officers, judges, legal practitioners, religious leaders, women's rights advocates, and social workers, while secondary data were obtained from legislation, court decisions, official reports, and relevant academic literature. The findings demonstrate that patriarchal culture continues to legitimize domestic violence as a private family matter, discouraging victims from seeking legal remedies and influencing institutional responses. The study also identifies a persistent justice gap characterized by inconsistent law enforcement, weak institutional coordination, inadequate victim protection, and social pressures that frequently divert criminal cases into private family settlements. These conditions undermine the effective enforcement of domestic violence legislation and contradict the principles of contemporary Islamic family law, particularly justice, human dignity, equality, and the protection of vulnerable family members. The study concludes that strengthening legal protection requires integrated law enforcement, institutional reform, victim-centered legal services, and the reconstruction of patriarchal norms through the values of contemporary Islamic family law. Academically, this research contributes an empirical socio-legal framework that integrates patriarchal culture, the justice gap, and contemporary Islamic family law, providing both theoretical insights and practical policy recommendations for improving domestic violence prevention and victim protection in Indonesia.